Employability and mobility in the valorisation of higher education qualifications: the experiences and reflections of Chinese students and graduates. Issue 3 (3rd May 2016) - Mok, Ka Ho; Wen, Zhuoyi; Dale, Roger
ABSTRACT: In the last two decades, we have witnessed a rapid expansion of higher education in Mainland China and Taiwan, recording a significant increase in higher education enrolments in these two Chinese societies. The massification of higher education in China and Taiwan has inevitably resulted in an oversupply of university graduates, with growing social concerns for skills mismatches being found in the labour market, stagnant graduate employment and social mobility. This article critically examines how university students and graduates in these two Chinese societies reflect upon their employment experiences. Human capital theory predicts that other things being equal, raising participation in higher education will initially increase inequality as rates of return rise, and then it will reduce inequality as expansion reaches mass levels and rates of return decline. If the output of graduates outpaces the demand for their skills, which appears to be the current case in many countries, then supply and demand pressures reduce the pay premium for degrees and lower income inequalities. However, this study clearly demonstrates that the massification and the universalisation of higher education in Mainland China and Taiwan, respectively, have actually intensified inequality.